School-based interventions for struggling readers, K-8 - Ortlieb, Evan; Cheek, Earl H. (Emerald, 2013)
The volume highlights best practices of literacy instruction for students who have difficulties in reading. From components of effective pedagogy to instruction for specific populations, this text offers an array of expert perspectives on how to engage, scaffold, and prepare students to meet the multimodal demands of schools today. Renowned authors promote the notion that with thoughtful literacy and purposeful approaches to reading instruction, all children have the ability to improve their reading proficiencies. Core literacy instruction targeting comprehension, fluency, vocabulary, and writing development among others is of particular focus while supplementary discussions of factors such as native language, diversity, inclusion, and learning disabilities fully characterize issues related to struggling readers for which evidence-based approaches are presented to foster lasting success. It conveys a current portrayal of issues and trends of school-based literacy practices appropriate for novice and experienced educators and researchers alike.
Keywords: Education -- Teaching Methods & Materials / Reading & Phonics.; Education -- Teaching Methods & Materials -- General.; Education -- Testing & Measurement.; Literacy strategies.; Educational strategies & policy.; Literacy -- Study and teaching.; elektronické knihy; electronic books